Modul Drupal untuk Single-Sign-On Link Eksternal - Kridalukmana, Rinta (Jurnal Sistem Komputer, 2011)
Recently enterprises tend to develop web-basedapplication to deal with their business process. Withnumerous applications, enterprise must manage user foreach application and how to access those application in agood manner. Application portal with single-sign-onapproach is one alternative in managing user and enterpriseapplications. Single-sign-on approach can reduce thenecessaries to remember login information to eachapplication by user. As a solution in web-based contentmanagement system, Drupal is one alternative to manageboth issues above. Combined with LDAP (LightweightDirectory Access Protocol) to support single-sign-onapproach, LDAP integration module for Drupal is needed.This module will authenticate user information from LDAPserver. After LDAP authentication, the next problem is howto use the authenticated user information to sign onenterprise application. Other module needs to be developedsolve the problem.